EVALUATION OF SUCCESSFUL MOBILE BANKING INFORMATION SYSTEM AT BANK SYARIAH INDONESIA - Nurlinda, RA; Bertuah, Eka (Jurnal Ekonomi dan Manajemen, 2022)
This study aims to determine what factors influence the success of the BSI Mobile banking application using the Delone and Mclean Information System Model. The variables used in this study are system quality, information quality, service quality, use, user satisfaction, and net benefit. This research was conducted on BSI customers who have done banking transactions using Mobile banking and have been BSI customers for the past year. The sample used is as many as 200 respondents with a sampling technique that is purposive sampling. This type of research is causal associative and the method used in this study is the Partial Least Square (PLS) method. Based on the results of research, information quality and service quality have a positive effect on user activity, system quality and information quality have a positive effect on user satisfaction, service quality does not affect user satisfaction, user activity has a positive effect on user satisfaction, user activity and user satisfaction have a positive effect on user benefits (net benefits). The results of this study are expected to help Bank Syariah Indonesia in improving the information system on Mobile banking so that it can provide satisfaction to BSI customers